Campur Kode Bahasa Bugis Ke Dalam Bahasa Indonesia di Sekolah MI DDI Al-Irsyad Long Iram Seberang Kutai Barat - Ahmad, M. Rusydi; Dulyana, Dulyana; Balfas, Anwar (Adjektiva: Educational Languages and Literature Studies, 2022)
This research is focused on mixing Bugis language codes into Indonesian at MI DDI Al-Irsyad Long Iram Seberang Kutai Barat School. The purpose of this study was to find out the forms of code mixing and to describe the factors for the formation of code mixing in Bugis and Indonesian in conversations at MI DDI Al-Irsyad Long Iram Seberang Kutai Barat. This study uses the method of observation, with techniques direct observation and notes. Then the results of the analysis are presented in the form of a description which contains code mixing, code mixing forms, and the factors that occur code mixing at MI DDI Al-Irsyad Long Iram Seberang Kutai Barat. The results of the study of mixing the Bugis language code into Indonesian at MI DDI Al-Irsyad Long Iram Seberang Kutai Barat, are as follows. First, there are 13 data found in the form of code mixing of Bugis language into Indonesian in speech events. Mix the code in the form of words as much as 6 data. There are 3 phrases. Second, the researchers found that the factors that cause code mixing are speaker factor 1, language factor 1, and familiarity factor 2. From the results of this study it can be concluded that in the conversation that took place at MI DDI Al-Irsyad Long Iram Seberang there was a form code mixing in the form of words and phrases. The cause of code mixing is the speaker factor and the language factor in the occurrence of code mixing as an interaction.